(untitled) (Rethinking Food Security Policy in Developing Economies, 2026)
Drawing on comparative experiences from developing countries, this chapter examines how food system governance shapes food security and why policy outcomes depend on the interaction of institutions, markets, political economy, and environmental conditions rather than agricultural production alone. It presents a conceptual framework linking policy instruments, intermediary systems, and structural constraints to key food security outcomes, including availability, access, nutrition, stability, and resilience. Evidence from initiatives such as Brazil's Bolsa Família, Indonesia's subsidy reforms, Vietnam's trade liberalization, and climate-smart agricultural practices demonstrates that policy success is highly context dependent and closely tied to institutional capacity and adaptive governance. The chapter identifies policy coherence, strong institutions, political feasibility, integrated planning, and continuous learning as the principal drivers of effective food system transformation. It further highlights the need to balance critical trade-offs between efficiency and equity, productivity and sustainability, and short-term relief and long-term resilience. The chapter concludes that there is no universal blueprint for achieving food security; instead, durable progress requires context-specific, flexible, and evidence-based policy frameworks that treat food systems as interconnected and dynamic systems.